Determinan Status Keterbukaan Diri Mahasiswa Tingkat Akhir - Muhammad Rifqi Wardana; Budyanra Budyanra (Politeknik Statistika STIS, 2021)
Final year students are required to compose a written work by applying the knowledge that has been obtained. The process of writing the final project requires guidance from a supervisor, but during a pandemic, learning activities are carried out online, including the guidance process, this becomes difficult for some students. The difficulty he faces is the lack of self-disclosure to the supervisor which, if the student's self-disclosure is low, it will hinder the preparation and guidance process. Zulkifli's research (2012) stated that 65 percent of the completion of the final project was hampered due to low self-disclosure, as well as STIS Polstat students who since the pandemic have also experienced online guidance. This study aims to provide an overview of the self-disclosure status and analyze the variables that affect the self-disclosure status of final year students of Polstat STIS Academic Year 2020/2021 by using binary logistic regression. The research data is primary data with a circular systematic sampling method. Based on the general description, it is known that final year students have low self-disclosure status as much as 22.88 percent and the rest have high status. From the logistic regression equation, it was found that the variables of student sex (OR = 2.35), self-esteem status (OR = 6.34), and personality type (OR = 2.62) with a significance level of five percent affected the self-disclosure status of final year students. Polstat STIS Academic Year 2020/2021.